Collective action management of Anticorruption Education (ACE) from an organizational sociology perspective: A proposed institutional strategy for ACE - Sari Angraeni (Komisi Pemberantasan Korupsi, 2024)
Anti-corruption Education (ACE) is an effort to instill integrity/anticorruption values in students at all levels of formal education, resulting in the improvement of integrity throughout the educational ecosystem. With the involvement of broad and diverse educational stakeholders, ACE is a complex collective action aimed at forming a society with integrity. This paper analyzes the social dynamics in the implementation of ACE with an institutional approach. The main focus is on the interaction between formal rules, social norms, and individual actions in the context of education. This paper shows that the success of ACE is not only determined by the existence of good policies and programs, but also by the strength of social networks, leadership, and shared understanding of anti-corruption values among stakeholders. These dynamics form a complex system in which changes to one element can have an impact on others. The final section presents conclusions and recommendations for stakeholder governance to enhance ACE’s operational effectiveness. These recommendations will be provided to KPK as the government agency mandated to organize Anti-corruption Education.